A meta-analysis study of the effect of the blended learning model on students’ mathematics learning achievement - Samritin Samritin; Aris Susanto; Abdul Manaf; Julham Hukom (Jurnal Elemen, 2023)
Many studies have researched the effect of blended learning on mathematics learning achievement, but the results of previous research reported different results. Therefore, this research aims to determine the effect of the blended learning model on mathematics learning achievement. The design of this study used a meta-analysis approach by analyzing 20 effect sizes from 18 primary studies that were Scopus-indexed and met the inclusion criteria. The results of the analysis show that the use of the blended learning model affects mathematics achievement compared to traditional learning (d = 0.725; p < 0.05). The results of the analysis according to the moderator variable are known that the effect of the blended learning model on mathematics achievement is different based on the level of education (Qb = 13.923; p < 0.05) and the year of research (Qb = 16.140; p < 0.05). However, no differences were found according to the sample size group (Qb = 0.039; p > 0.05) and media platform (Qb = 2.861; p > 0.05. The findings show the consistency of the publication of research results on the effect of using the blended learning model on students' mathematics learning achievement.